Społeczna odpowiedzialność uczelni wyższych = The social responsibility of higher education institutions - Cybal-Michalska, Agnieszka (Zielona Góra: Lubuskie Towarzystwo Naukowe)
In the context of the contemporary world changes, the issue of social responsibility including the social responsibility of higher education institution deserves special attention. The category of responsibility in the social context underlines the importance of interest in social life subjects resulting from the process of maturation of the awareness of the society needs. In the public spirit issues found in the functioning of higher education institution, a special attention is drawn to the activity of academic circles based on a set of values, norms of behaviour and the practice to aspire to the truth, as the constitutive values for science, researchers and scientists is above all the truth, the search for it, its description and its discovery.
Keywords: szkolnictwo wyższe; uczelnia wyższa; uczelnia społecznie odpowiedzialna